Pelatihan Membuat Tasbih Pada Siswa Tunagrahita Di SLB YP3LB Makassar - Bastiana Bastiana; Tatiana Meidina; Andi anggi Ade Putri; Nurlaelatul Jannah; Nurlailah Nurlailah; Widianti Widianti (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
SLB must prepare its graduates to have adequate income for themselves. One simple skill that is expected to provide income is tasbih making. This community service activity is carried out through training activities on making simple prayer beads for intellectual disability students at SLB YP3LB Makassar. Implementation of service using the demonstration method. The presenter introduces materials and tools then demonstrates how to make simple tasbih, after which the presenter guides step by step how to make tasbih. Participants in the service activity were intellectual disability students in class 11 SLB YP3LB Makassar, totaling 5 people. Community service activities can be carried out properly. Intellectual  disability students can make simple tasbih even with the help of activity companion students. It is recommended to prepare students' initial abilities before providing training. It is hoped that this training can be continued with tasbih that are more varied and have a sale value